Dataset used in the article "Balancing Forage and Fear: How people, environment and predators shape reindeer grazing in the Fennoscandian tundra" - Stoessel, Marianne; Wikinger, Felicia; Lindborg, Regina (Stockholm University, 2026)
The datasets provided are grazing activity data and location data recorded from loggers deployed on 31 reindeer in three Swedish herding districts, during the summers 2019 and 2020. It is the data used for the study presented in the manuscript "Balancing Forage and Fear: How people, environment, and predators shape reindeer grazing in the Fennoscandian tundra".

The datasets are given in one R datafile "Stoessel_et_al_Data". An R script, entitled "S5_Supplementary_RSourceCode" that includes the final steps of the habitat-selection function (HSF) analysis and the grazing analysis for the three herding districts.

Note: Since the reindeer activity data come from loggers deployed on semi-domesticated reindeer owned by reindeer herders, the raw GPS data belong to the herding communities who collaborated on this project and is not given direct public access. Please contact the corresponding author if you wish to get access to it (email address: marianne.stoessel@natgeo.su.se (mailto:marianne.stoessel@natgeo.su.se) ).
Keywords: Behavioural ecology; Landscape ecology; Impacts of tourism; Ecology; Ekologi